Persepsi Guru terhadap Integrasi TPACK dalam Pembelajaran IPS di Sekolah Dasar - Diki Somantri; Siti Komala Putri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to find out how teachers perceive the implementation of TPACK in current social studies learning. Learning has now entered the 21st century which requires teachers to be able to have communication and collaboration skills as well as utilize technology in the learning process within a framework in the form of TPACK. There are 7 components that need to be known in TPACK, including Technological Knowledge, Pedagogical Knowledge, Content Knowledge, Technological Pedagogical Knowledge, Technological Content Knowledge, Pedagogical Content Knowledge, and Technological Pedagogical Content Knowledge. The purpose of this article is to find out the views or perceptions of teachers in implementing TPACK in elementary school social studies learning. This research method uses library research, namely a method with a data collection process by understanding and studying theories from various literature study sources related to research issues or problems. The results of the research are that teachers' perceptions regarding the implementation of TPACK are very important and the components in the TPACK section need teachers to understand and apply them to students in the 21st century learning process.